Comparison of Two Fluid Replacement Protocols During a 20-km Trail Running Race in the Heat. Issue 9 (September 2016) - Lopez, Rebecca M.; Casa, Douglas J.; Jensen, Katherine A.; Stearns, Rebecca L.; DeMartini, Julie K.; Pagnotta, Kelly D.; Roti, Melissa W.; Armstrong, Lawrence E.; Maresh, Carl M.
Abstract : Abstract: Lopez, RM, Casa, DJ, Jensen, K, Stearns, RL, DeMartini, JK, Pagnotta, KD, Roti, MW, Armstrong, LE, and Maresh, CM. Comparison of two fluid replacement protocols during a 20-km trail running race in the heat. J Strength Cond Res 30(9): 2609–2616, 2016—Proper hydration is imperative for athletes striving for peak performance and safety, however, the effectiveness of various fluid replacement strategies in the field setting is unknown. The purpose of this study was to investigate how two hydration protocols affect physiological responses and performance during a 20-km trail running race. A randomized, counter-balanced, crossover design was used in a field setting (mean ± SD : WBGT 28.3 ± 1.9° C). Well-trained male ( n = 8) and female ( n = 5) runners (39 ± 14 years; 175 ± 9 cm; 67.5 ± 11.1 kg; 13.4 ± 4.6% BF) completed two 20-km trail races (5 × 4-km loop) with different water hydration protocols: (a) ad libitum (AL) consumption and (b) individualized rehydration (IR). Data were analyzed using repeated measures ANOVA. Paired t -tests compared pre-race–post-race measures. Main outcome variables were race time, heart rate (HR), gastrointestinal temperature (TGI ), fluid consumed, percent body mass loss (BML), and urine osmolality (Uosm ). Race times between groups were similar. There was a significant condition × time interaction ( p = 0.048) for HR, but TGI was similar between conditions. Subjects replaced 30 ± 14% of their water losses in AL and 64 ± 16% of their losses in IR ( p < 0.001). Ad libitum trial experienced greater BML (−2.6 ± 0.5%) compared with IR (−1.3 ± 0.5%; p < 0.001). Pre-race to post-race Uosm differences existed between AL (−273 ± 146 mOsm) and IR (−145 ± 215 mOsm, p = 0.032). In IR, runners drank twice as much fluid than AL during the 20-km race, leading to > 2% BML in AL. Ad libitum drinking resulted in 1.3% greater BML over the 20-km race, which resulted in no thermoregulatory or performance differences from IR.